2013
DOI: 10.7314/apjcp.2013.14.12.7639
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Breast Cancer Early Detection Services Provided through Well Woman Clinics in the District of Gampaha in Sri Lanka

Abstract: Background: Breast cancer is the most common cancer diagnosed among women in Sri Lanka. Early detection can lead to reduction in morbidity and mortality. The objective here was to identify perceptions of public health midwives (PHMs) on the importance of early detection of breast cancer and deficiencies of and suggestions on improving existing breast cancer early detection services provided through Well Woman Clinics. Materials and Methods: A qualitative study using four focus group discussions (FGDs) were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The treatment costs of female reproductive system malignancies (including breast cancer) is a considerable burden to government healthcare expenditure and premature deaths of females are an irreplaceable loss to their families and workforce. Recognizing the importance of early detection and treatment of female reproductive tract cancers, successive governments in Sri Lanka have initiated and funded community based health education and early detection/screening programmes mainly through “well woman clinics” [ 3 ]. While the positive impact of these interventions are obvious (early detection via standard screening measures such as Papanicolaou (Pap) smear for cervical cancer), the numbers of female reproductive system malignancies in Sri Lanka are still significant and increasing [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment costs of female reproductive system malignancies (including breast cancer) is a considerable burden to government healthcare expenditure and premature deaths of females are an irreplaceable loss to their families and workforce. Recognizing the importance of early detection and treatment of female reproductive tract cancers, successive governments in Sri Lanka have initiated and funded community based health education and early detection/screening programmes mainly through “well woman clinics” [ 3 ]. While the positive impact of these interventions are obvious (early detection via standard screening measures such as Papanicolaou (Pap) smear for cervical cancer), the numbers of female reproductive system malignancies in Sri Lanka are still significant and increasing [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches, including breast self-examination (BSE), regular mammography, and clinical breast examination (CBE) (Avci 2008), have been adopted for improving early detection rate. However, regular mammography and CBE may not be practical in developing countries, as there are still lacking of health insurances and having a low rate of regular mammography (Memon et al, 2013;Vithana et al, 2013;Yoo et al, 2013), making BSE as the alternative approach.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that cultural beliefs, health practices, fear, lack of knowledge, social barriers, the stigma of the diagnosis of breast cancer, and the level of education were all contributory factors that hindered screening and early detection of breast cancer. [678910]…”
Section: Introductionmentioning
confidence: 99%